Membangun Motivasi Menabung Anak LKSA Aisyiyah Kota Bengkulu Melalui Kreasi Barang Bekas - Dienti, Arlita; Feni, Rita; Marwan, Edy; Yawahar, Jon; Mulyadi, Maheran; Efrita, Edi (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Saving is one of the way to take control of financial, fulfill daily needs, train to live frugally, train to live independently and smartly control financial from early age and hopefully will be carried away until adult. This service aims to expand the knowledge on the importance of saving and to teach how to make piggy bank to save money. Target for this service are the kids from LKSA ‘Aisyiyah Kasih Ibu. LKSA is a children social welfare program from ‘Asyiyah Kasih Ibu orphanage in Bengkulu city. This service method include 1). Socialization about the function and method of saving and how to make piggy bank from used materials 2). A demonstration on how to make a piggy bank from used card box and bottle. The result of this service shows enthusiasm of participants. This service is also expand the knowledge and skill of the participants. This activity not only gives motivation, but also a new skill to apply saving habit in daily life.